Collagen Ⅵ‐related myopathy with subacute presentation of hypercapnic respiratory failure following pneumonia. Issue 5 (23rd June 2020) - Kinboshi, Masato; Nakaoka, Hiroshi; Morimoto, Yuko; Yoshida, Takeshi; Kuzume, Daisuke; Shiraga, Minoru; Ishida, Masayuki; Yamasaki, Masahiro; Saito, Yoshihiko; Nishino, Ichizo
Abstract: Bethlem myopathy, the mild form of collagen Ⅵ‐related myopathy, gradually affects pulmonary function without causing symptoms. We report a case of a 38‐year‐old woman presenting with subacute deterioration of hypercapnic respiratory failure following pneumonia. She had posterior instrumentation and fusion for scoliosis during adolescence. Mild muscle weakness of trunk and proximal lower limbs, representing atrophic changes in imaging, and flexion contractures were present. The muscle pathology showed moderate variation in fiber size with mild endomysial fibrosis. The heterozygous COL6A1 mutation was identified. We made the diagnosis of collagen Ⅵ‐related myopathy. Noninvasive positive pressure ventilation improved the respiratory failure.